OBTURATOR HERNIA: A DIAGNOSTIC DILEMMA, REPORT OF A CASE - (:unkn) unknown (My University, 2014)
Obturator herni yaşlı, zayıf ve multipar kadınlarda görülen nadir bir pelvik herni türüdür.Hastalar nonspesik klinik bulgular taşımaktadırlar ve tanıda genellikle gecikmeler ya da hatalar yaşanmaktadır. Bu hernilerin tanısal zorluğu, fıtık kesesinin pektineus kası tarafından gizlenmesinden kaynaklanmaktadır; hekimler yaşlı kadın hastalarda ayırıcı tanıda obturator herniyiakılda tutmalıdır. Erken tanı ve müdahale ile cerrahi komplikasyon riski azaltılabilir ve sürvi şansıartırılabilir. Fizik muayeneye ek olarak, ultrason, herniografi ve de Bilgisayarlı Tomografi gibi radyolojik tetkikler tanıda yardımcı incelemeler olarak öne sürülmüştür. Bu makalede 78 yaşında obturator herniye bağlı uyluk ağrısı ile başvuran bir olgu sunulmaktadır. Bu vakada manyetik rezonansgörüntüleme ile tanı doğrulanmıştır

Obturator hernia is a rare pelvic hernia that occurs in elderly, thin, multiparous women.Patients present with few nonspecific clinical symptoms to identify the cause, and the diagnosis is often delayed or missed. Physicians should maintain a high level of clinical suspicion forobturator hernia in elderly women as it is a diagnostic challenge in which the hernia mass is usually concealed beneath the pectineus muscle. Early diagnosis and prompt initiation of treatmentreduces the risk of surgical complications and increases the chance of survival. Different imagingmodalities including Ultrasound, herniography and CT have been proposed to assist with accurate diagnosis. Herein, we present a case of a 78 year-old woman with thigh pain secondary toan obturator hernia and magnetic resonance imaging confirmed the diagnosis
OBTURATOR HERNİ: TANISAL İKİLEM, BİR OLGU SUNUMU
Keywords: Cerrahi